Epstein–Barr virus associated CNS lymphoproliferative disorder after long-term immunosuppression. Issue 1 (29th August 2019) - Lee, Andrew; Bridges, Leslie R; Lloyd, Mark; Barker, Robert; Wren, Damian R; Galtrey, Clare M
Abstract : The incidence of Epstein–Barr virus (EBV)associated lymphoproliferative disorders has increased with greater use of immunomodulatory therapies. We present a woman who developed subacute cognitive decline and unilateral weakness while taking long-term mycophenolate mofetil for granulomatosis with polyangiitis; her postmortem brain histopathology confirmed an EBV-driven lymphoproliferative disorder. Clinicians must have a high index of suspicion for EBV-driven lymphoma in people taking long-term immunosuppression who develop new neurological problems. We review the role of mycophenolate mofetil in EBV-driven lymphoproliferative disorders, and discuss checking EBV status in all patients starting immunosuppression and in older people already taking immunosuppression.